2009
DOI: 10.1007/s11425-008-0150-8
|View full text |Cite
|
Sign up to set email alerts
|

The quantum general linear supergroup, canonical bases and Kazhdan-Lusztig polynomials

Abstract: Canonical bases of the tensor powers of the natural Uq(gl m|n )-module V are constructed by adapting the work of Frenkel, Khovanov and Kirrilov to the quantum supergroup setting. This result is generalized in several directions. We first construct the canonical bases of the Z2-graded symmetric algebra of V and tensor powers of this superalgebra; then construct canonical bases for the superalgebra Oq(M m|n ) of a quantum (m, n) × (m, n)-supermatrix; and finally deduce from the latter result the canonical basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…Our categorification relies on a very careful analysis of the representation theory of gl(1|1) and its canonical basis (based on [Zha09]). In the categorification, indecomposable projective modules correspond to canonical basis elements, that we can compute explicitly via a diagram calculus, analogous to the diagram calculus developed in [FK97] for sl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%